Translational research. Prospects in Russia - A. S. Kolbin; R. A. Gapeshin; S. M. Malyshev (Регуляторные исследования и экспертиза лекарственных средств)
In recent years health care professionals came to understanding that any medical technology should be a subjected of expert evaluation. One of the key issues in the evaluationt of medical technologies is the ability to transfer effectiveness data to efficacy. Effectiveness and efficacy are also a part of translational (operational) research, transferring from basic knowledge to clinical practice. Effectiveness and efficacy studies, as well as translational research usually allow to evaluate the reasonability of the use of medical technology in a defined group of population in terms of clinical outcomes and costs. The problem of fragmented biomedical data can be solved by means of conducting translational (operational) research in which medical technology is evaluated from the perspective of fundamental science. The translation process takes quite a long time, but eventually gives a holistic and comprehensive idea about the investigational medical technology, which will allow its correct implementation into clinical practice and health care system.